The Investigation of Suitable Varieties for Autumn-Sown of Sugar Beet in the Warm Region of Kermanshah Province - Ali Jalilian; Yasin Norouzi; Danial Kahrizi; Mandana Azhand; Anita Yaqotipour; Marcello Iriti (Agrotechniques in Industrial Crops)
One of the most suitable areas for autumn beet cultivation is the tropical regions of Kermanshah province, which requires new cultivars appropriate for cultivation in these regions to be identified and introduced every year. For this purpose, an experiment including 10 sugar beet cultivars named Rosegold, Ratna, Silota, Jera, Beaufort, Rozanab, Barossa, FD15131014, BTS4770 and Joncal was conducted based on a randomized complete block design with four replications in Sarpol Zahab city, 2019. Each plot consisted of three eight-meter rows, with a row distance of 50 cm and the distance between the plants after thinning was 20 cm. Planting was done by hand. The Bolting percentage was recorded before harvest. At the time of harvest, root yield and quality characteristics including the percentage of sugar, sodium, nitrogen and potassium were measured, and the yield of pure and impure sugar and molasses sugar was calculated. The results showed that the yield of investigated cultivars (Rosagold, Beaufort, Gera, Ratna and Uncal) was 111, 116, 114, 105 and 119 tons per hectare with an average of 13-13.5% sugar and bolting was less than 7%. In the year of the experiment, the variety that had the largest cultivated area in the Sarpol Zahab area was the rosegold variety, but the Beaufort, Jara, Ratna, and Jankal varieties had performance and quality equal to or greater than this variety. The bolting percentage was below 3%. The four new varieties of sugar beet are better or equal to the rosegold variety and are recommended for cultivation in the tropical regions of Kermanshah province as an autumn crop.